Quantifying the Degree of Movement Dissimilarity between Two Distinct Action Scenarios: An Exploratory Approach with Procrustes Analysis - Passos, Pedro; Campos, Tania; Diniz, Ana (Frontiers in Psychology, 2017)
Game consoles allow subjects to perform movements which are visually similar to the movements performed in ‘real’ world scenarios. Beyond entertainment, virtual reality devices are being used in several domains: sports performance; motor rehabilitation; training of risk professions. This article presents the Procrustes method to measure the degree of dissimilarity between movements performed in ‘real’ and ‘virtual’ scenarios. For this purpose, the 501 darts game and a video darts game played on a console were used. The participants’ arm throwing movements were video recorded and digitized. The matrices of x and y coordinates of the movements of the wrist, elbow, and shoulder in both performance scenarios were subjected to the Procrustes method. The wrist displays the most extreme dissimilarity values (higher than elbow and shoulder). Results also revealed smaller dissimilarity values for movements performed under the same conditions (e.g., real-real) and larger dissimilarity values between movements performed in different scenarios.